2016
DOI: 10.1002/2016jb013020
|View full text |Cite
|
Sign up to set email alerts
|

Seismic anisotropy of the lithosphere and asthenosphere beneath southern Madagascar from teleseismic shear wave splitting analysis and waveform modeling

Abstract: Madagascar occupies a key position in the assembly and breakup of the supercontinent Gondwana. It has been used in numerous geological studies to reconstruct its original position within Gondwana and to derive plate kinematics. Seismological observations in Madagascar to date have been sparse. Using a temporary, dense seismic profile across southern Madagascar, we present the first published study of seismic anisotropy from shear wave splitting analyses of teleseismic phases. The splitting parameters obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 52 publications
3
38
0
Order By: Relevance
“…Another potential source of the seismic anisotropy in southern Madagascar is fossil anisotropy in the entire lithosphere as suggested by Reiss et al (). In the south central region and part of southeastern region, the geology is characterized by the Ranotsara shear zone that was active during the East African Orogeny 500 Ma (e.g., de Wit et al, ).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Another potential source of the seismic anisotropy in southern Madagascar is fossil anisotropy in the entire lithosphere as suggested by Reiss et al (). In the south central region and part of southeastern region, the geology is characterized by the Ranotsara shear zone that was active during the East African Orogeny 500 Ma (e.g., de Wit et al, ).…”
Section: Discussionmentioning
confidence: 94%
“…Comparison of synthetic splitting (white bars) derived from lithosphere‐mantle wind interactions models with SKS splitting measurement bars colored according to angular misfit (0–90°; Ramirez et al, ; Reiss et al, ) (a) for Behn et al () global mantle flow and (b) for (Forte et al, ) global mantle flow. Gray wedges represent confidence interval associated with the synthetic splitting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, they found that the central part of Madagascar is thinner (∼39 km) than the eastern coast (∼44 km). Additional information on crustal structure comes from a recent study of SKS splitting along the SELASOMA profile showing strong crustal anisotropy of up to 12 per cent in a 150 km broad zone located along the shear zones in southern Madagascar (Reiss et al 2016).…”
Section: Previous Studies Of the Crust Of Madagascarmentioning
confidence: 99%